K.H. Hasyim Asy’ari dan Urgensi Riyâdah dalam Tasawuf Akhlâqî - Abdullah Hakam (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2014)
This article explores the K.H. Hasyim Asy’ari and the urgency of riyâdah in tasawuf akhlâqî. The forms of riyâdah of Kiai Hasyim in tasawuf akhlâqî are: pilgrimage to the Cave of Hira, pilgrimage at the tomb of the Prophet Muhammad, frequent fasting and eating little, praying Tahajjud, maintaining friendship with the neighbors, performing Tarâwih prayer by reciting the whole al-Qur’ân, praying Istikhârah frequently, always keeping the congregational prayers, and practicing wird qunût nâzilah and hizb al-falâh. The reason and purpose of riyâdah conducted by Kiai Hasyim is to remember the struggle of the Prophet, to implement the Sunnah of the Prophet, to prevent lust temptation, to draw closer to God, and for the propagation of Islam. Moreover, the reason and the core objective of various riyâdah conducted by Kiai Hasyim is to draw closer to God by concentrating on coaching about morality and soul treatment.